7.2 PSYCHOTIC LIKE EXPERIENCES AND THEIR ASSOCIATIONS IN SEVEN-YEAR-OLD CHILDREN WITH FAMILIAL HIGH RISK OF SCHIZOPHRENIA OR BIPOLAR DISORDER. (9th April 2019) - Ellersgaard, Ditte; Gregersen, Maja; Hemager, Nicoline; Christiani, Camilla Jerlang; Burton, Birgitte Klee; Spang, Katrine; Møllegaard Jepsen, Jens Richardt; Mors, Ole; Plessen, Kerstin von; Thorup, Anne Amalie; Nordentoft, Merete
Abstract: Background: Psychotic like experiences (PLEs) are frequently found among children from the general population. PLEs are often transitory phenomena, but are for some predictive of later psychopathology, e.g. psychotic disorders and non-psychotic disorders. For both schizophrenia and bipolar disorder, the single largest risk factor for developing the disorder is a positive family history of the disorder. Therefore, early antecedents of schizophrenia and bipolar disorder can be identified by studying children of parents with these disorders. However, little is known of the occurrence of PLEs in children with familial high risk of schizophrenia (FHR-SZ) and bipolar disorder (FHR-BP). We aimed to explore PLEs and their associations to mental disorders and level of functioning in young children with FHR-SZ and FHR-BP compared with controls. Methods: The Danish High Risk and Resilience Study – VIA7 is a population-based cohort study. We retrieved a representative cohort of seven-year-old children with FHR-SZ (N=202), FHR-BP (N=120), and population-based controls(N=200) using Danish nationwide registers. PLEs were assessed through interview with the psychosis appendix of the 'Schedule for Affective Disorders and Schizophrenia for School-Age Children - Present and Lifetime Version' (K-SADS-PL). Both children and primary caregivers were interviewed. Lifetime DSM-IV diagnoses were identified by interview with the K-SADS-PL. The general level of functioning was assessed with the Children's Global Assessment Scale. Results: The three groups displayed clear differences in the prevalence of PLEs. Additionally, the associations between PLEs and psychopathology as well as level of functioning are explored. These findings will be presented at the session. Conclusions: Our findings suggest that further studies of the long-term implications of PLEs in young children with familial high risk of severe mental disorders are needed. In particular with regard to the effect of PLEs on general level of functioning and mental health of these children.